Bioavailability of anthocyanins and colonic polyphenol metabolites following consumption of aronia berry extract. (15th November 2016) - Xie, Liyang; Lee, Sang Gil; Vance, Terrence M.; Wang, Ying; Kim, Bohkyung; Lee, Ji-Young; Chun, Ock K.; Bolling, Bradley W.
Highlights: Consumption of 500 mg aronia berry extract increased plasma and urine polyphenols. Peonidin-3- O -galactoside was a significant anthocyanin metabolite in plasma and urine. Anthocyanins and colonic catabolite tmax values were from 1 to 6.3 h. Colonic polyphenol catabolites exceeded anthocyanin precursors in plasma and urine. Abstract: A single-dose pharmacokinetic trial was conducted in 6 adults to evaluate the bioavailability of anthocyanins and colonic polyphenol metabolites after consumption of 500 mg aronia berry extract. UHPLC-MS methods were developed to quantitate aronia berry polyphenols and their metabolites in plasma and urine. While anthocyanins were bioavailable, microbial phenolic catabolites increased ∼10-fold more than anthocyanins in plasma and urine. Among the anthocyanins, cyanidin-3- O -galactoside was rapidly metabolized to peonidin-3- O -galactoside. Aronia polyphenols were absorbed and extensively metabolized with tmax of anthocyanins and other polyphenol catabolites from 1.0 h to 6.33 h in plasma and urine. Despite significant inter-individual variation in pharmacokinetic parameters, concentrations of polyphenol metabolites in plasma and urine at 24 h were positively correlated with total AUC in plasma and urine (r = 0.93, and r = 0.98, respectively). This suggests that fasting blood and urine collections could be used to estimate polyphenol bioavailability and metabolism after aronia polyphenol consumption.